Clinical features and mutational analysis in 114 young children with Wilson disease from South China. Issue 8 (6th June 2019) - Li, Xiuzhen; Lu, Zhikun; Lin, Yunting; Lu, Xinshuo; Xu, Yi; Cheng, Jing; Shao, Yongxian; Su, Xueying; Liu, Zongcai; Sheng, Huiying; Cai, Yanna; Li, Taolin; et al.
Abstract: Wilson disease (WD) is a rare autosomal recessive disorder caused by mutations in the ATP7B gene. Clinical features and mutational analysis of Chinese children with WD at early age were rarely described. Herein, we retrospectively examined 114 children with WD at the mean of 5.9 years old age at diagnosis. Eight patients developed acute liver failure at mean age of 9.7 years old, 4 of whom died. Among the 114 patients, 86.0% were presymptomatic with isolated elevation of transaminases at diagnosis, 99.1% had decreased ceruloplasmin, and 68.4% had urinary copper excretion over 100 μg/24 hr. Bi‐allele pathogenic ATP7B mutations were identified in all patients. Among the 60 mutations detected, 10 were novel, including 7 missense mutations (p.I566N, p.T704I, p.C980F, p.G1030 V, p.A1096Q, p.L1327P, and p.L1373F), 1 nonsense mutation (p.K866X), 1 small insertion (p.Y44LfsX2), and 1 small deletion (p.R1118PfsX10). The most frequent mutations were p.R778L, p.P992L, and p.I1148T, which affected 27.2, 25.4, and 20.2% of the 114 WD children, respectively. The patients carrying p.R778L presented a higher rate of acute liver failure than the patients without p.R778L (9.7% vs. 4.8%). These results will be helpful in establishing early diagnosis of WD at the gene level, offering beneficial information for genetic counseling and providing clues to genotype/phenotype correlation of ATP7B mutations.